2019
DOI: 10.1556/030.66.2019.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of Acanthamoeba keratitis by genotypes T4 and T8 in Hungary

Abstract: Genus Acanthamoeba is an opportunistic protozoan that is widely distributed in the environment. Within this genus, numerous species are recognized as human pathogens, potentially causing Acanthamoeba keratitis (AK). AK is a corneal disease, associated predominantly with contact lens (CL) wear; its epidemiology is related to the specific Acanthamoeba genotypes. This study reports seven CL wearer, Acanthamoeba PCR-positive patients with AK, diagnosed between January 2015 and 2018. Patients had the diagnosis of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…50 It should be also noticed that, in our study, only one Acanthamoeba isolate was analyzed, and it cannot be excluded that other Acanthamoeba genotypes may respond to the tested drugs in a different way. 51 Experiments are ongoing in our laboratories to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…50 It should be also noticed that, in our study, only one Acanthamoeba isolate was analyzed, and it cannot be excluded that other Acanthamoeba genotypes may respond to the tested drugs in a different way. 51 Experiments are ongoing in our laboratories to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to data on Acanthamoeba infections in humans, little is known about infections in rhizosphere. It has been concluded that the rhizosphere isolates are most closely related to strains commonly isolated from human infections, especially AK [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The T4 is commonly described in GAE cases; however, other genotypes such as T1, T2, T5, T10, T12, and T18 have been related to this disease [ 9 ]. In Table 2 , the classification is broken down into the representative strains; the current distribution of genotypes and morphology worldwide of the Acanthamoeba spp., including those isolated from clinical cases and environmental samples, can be seen in Figure 2 [ 6 , 44 , 50 , 52 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. Finally, the recent cases in databases are described in Table 3 .…”
Section: Acanthamoeba Sppmentioning
confidence: 99%